2020
DOI: 10.1155/2020/1841527
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Prevents Right Ventricle Remodeling and Dysfunction in Monocrotaline-Induced Pulmonary Arterial Hypertension with a Limited Improvement in the Lung Vasculature

Abstract: Pulmonary arterial hypertension (PAH) is a life-threatening disease that is characterized by an increase in pulmonary vascular pressure, leading to ventricular failure and high morbidity and mortality. Resveratrol, a phenolic compound and a sirtuin 1 pathway activator, has known dietary benefits and is used as a treatment for anti-inflammatory and cardiovascular diseases. Its therapeutic effects have been published in the scientific literature; however, its benefits in PAH are yet to be precisely elucidated. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 59 publications
0
28
0
Order By: Relevance
“…In this sense, winery by-products have been successfully used to obtain antioxidant [ 31 ], antimicrobial [ 32 ], anti-inflammatory [ 33 ], antihyperglycemic [ 34 ], or antihypertensive compounds [ 14 , 16 , 17 , 35 ]. For instance, extracts rich in phenolic compounds (proanthocyanidins or resveratrol), with antihypertensive properties in both rats and humans, have been extracted from stem, grape seeds, or skin, respectively [ 13 , 15 , 16 , 17 , 36 , 37 , 38 ]. However, to our knowledge, no studies have been performed to evaluate whether WL can present ACEi or antihypertensive properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, winery by-products have been successfully used to obtain antioxidant [ 31 ], antimicrobial [ 32 ], anti-inflammatory [ 33 ], antihyperglycemic [ 34 ], or antihypertensive compounds [ 14 , 16 , 17 , 35 ]. For instance, extracts rich in phenolic compounds (proanthocyanidins or resveratrol), with antihypertensive properties in both rats and humans, have been extracted from stem, grape seeds, or skin, respectively [ 13 , 15 , 16 , 17 , 36 , 37 , 38 ]. However, to our knowledge, no studies have been performed to evaluate whether WL can present ACEi or antihypertensive properties.…”
Section: Discussionmentioning
confidence: 99%
“…Grapes are one of the world’s largest fruit crops and the wine production process generates large amounts of by-products [ 12 ]. Some winery by-products, such as grape seeds and skin, have already been used as a source for the extraction of phenolic compounds with numerous health benefits, including antihypertensive properties [ 13 , 14 , 15 , 16 , 17 ]. However, the presence of antihypertensive compounds in other winery by-products as wine lees (WL) remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Other antioxidants, such as quercetin and resveratrol, have been useful in preventing cellular damage and preserving mitochondrial functioning upon challenge with insults in vitro models, such as I/R ( Lozano et al, 2019 ), and in reducing right-heart remodeling and dysfunction in a murine model of pulmonary arterial hypertension ( Vázquez-Garza et al, 2020 ). Regarding arrhythmias, treatment with quercetin has proven useful in preventing platelet aggregation and arrhythmias in an I/R murine model.…”
Section: Novel Targets In Sr-mitochondria Interconnection As Potentiamentioning
confidence: 99%
“…It was previously thought that antioxidants like quercetin and resveratrol, due to their low bioavailability and non-specificity to any tissue, would make them poor candidates for new therapies ( Formica and Regelson, 1995 ). This is backed by the fact that only limited benefits have been found when using such therapies ( Askari et al, 2012 ; Wilson et al, 2016 ; Vázquez-Garza et al, 2020 ). Nonetheless, similar to the gene therapy described previously, the development of nanomaterials capable of packaging the components, protecting them from degradation, and directing them to a specific tissue places these often-dismissed compounds back on the table.…”
Section: Novel Targets In Sr-mitochondria Interconnection As Potentiamentioning
confidence: 99%
“…Several studies reported that resveratrol possessed antioxidant [ 23 ], anti-inflammatory [ 24 ], and proapoptotic activity [ 25 ]. Dietary polyphenol, resveratrol, has potential to improve endothelial dysfunction and decrease overall blood pressure [ 5 , 26 ]. In the hypertensive condition, resveratrol decreases vascular oxidative stress by scavenging H 2 O 2 and preventing oxidative stress-induced endothelial cell death [ 27 ].…”
Section: Introductionmentioning
confidence: 99%